0 ≤ k < r ≤ n + 1 ∑ ( k n ) ( r n + 1 )
Find the value of the summation above in terms of n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@Mark Hennings , we really liked your comment, and have converted it into a solution.
excellent solution indeed
Beautiful.
S = 0 ≤ k < r ≤ n + 1 ∑ ( n k ) ( n + 1 r ) = k = 0 ∑ n r = k + 1 ∑ n + 1 ( n k ) ( n + 1 r ) = k = 0 ∑ n ( n k ) ( 2 n + 1 − r = 0 ∑ k ( n + 1 r ) ) = 2 2 n + 1 − S ⇒ 2 S = 2 2 n + 1 o r S = 2 2 n
At the point where you state that the sum is equal to 2 2 n + 1 − S , you have equated the sum for r ≤ k with the sum for r > k . Just as with the other proofs given, that probably needs a sentence of justification.
@Aditya Dhawan , we have converted your comment into a solution.
The given sum is ∑ 0 ≤ k < r ≤ n + 1 ( k n ) ( r n + 1 )
This can be grouped as
( ( 0 n ) ( 1 n + 1 ) + ( 1 n ) ( 2 n + 1 ) + . . . . . . + ( n n ) ( n + 1 n + 1 ) ) +
( ( 0 n ) ( 2 n + 1 ) + ( 1 n ) ( 3 n + 1 ) + . . . . . . + ( n − 1 n ) ( n + 1 n + 1 ) ) +............
( ( 0 n ) ( n + 1 n + 1 ) )
now each of the brackets represent the coefficients of positive powers of x in the expansion of
( 1 + x 1 ) n × ( 1 + x ) n + 1
now this expression can be simplified as
( 1 + x 1 ) n × ( 1 + x ) n + 1 = ( ( 1 + x 1 ) × ( 1 + x ) ) n ( 1 + x ) = ( 2 + x + x 1 ) n ( 1 + x ) = ( x x 2 + 2 x + 1 ) n ( 1 + x ) = x n ( 1 + x ) 2 n + 1
we need to find the sum of coefficients of positive powers of x , there are 2 n + 2 terms in the expansion and we need to find the sum of coefficients of the last n + 1 terms
we know ( r n ) = ( n − r n )
Thus the sum of coefficients of first n + 1 terms will be same as sum of coefficients of final n + 1 terms
Total sum of coefficients= 2 2 n + 1
thus sum of coefficients of final n+1 terms is 2 2 2 n + 1 = 2 2 n = 4 n
Here is a solution that is similar to Mark's, but more directly presented.
The expression is equivalent to the number of ways that A can toss n coins and B can toss n + 1 coins, where the number of heads that A gets is strictly fewer than the number of heads that B gets.
We will create a double-counting bijection in the following way:
Let
A
toss
n
coins and
B
toss
n
+
1
coins. There are
2
n
×
2
n
+
1
ways to do so.
If A has strictly fewer heads than B, that is the case that we want to count.
If A has at least as many heads as B. Say
A
flipped
a
heads and
B
flipped
b
heads with
a
≥
b
. If we filp
all
of the coins, then
A
has
n
−
a
heads and
B
has
n
+
1
−
b
heads. Since
n
−
a
≤
n
−
b
<
n
+
1
−
b
, hence we are also back in the case that we want to count.
Conversely, given any "A gets strictly fewer heads than B", we can map it to these 2 cases, by flipping no coins and flipping all the coins.
Hence, the number of ways is 2 1 × 2 2 n + 1 = 2 2 n = 4 n .
[ This comment has been converted into a solution ]
S = 0 ≤ k < r ≤ n + 1 ∑ ( k n ) ( r n + 1 )
S = 0 ≤ k < r ≤ n + 1 ∑ ( n − k n ) ( ( n + 1 ) − r n + 1 )
Adding the two equations, we have
2 S 2 S 2 S 2 S S = 0 ≤ k ≤ n , 0 ≤ r ≤ n + 1 ∑ ( k n ) ( r n + 1 ) = ( 0 ≤ k ≤ n ∑ ( k n ) ) ( 0 ≤ r ≤ n + 1 ∑ ( r n + 1 ) ) = ( 2 n ) ( 2 n + 1 ) = 2 2 n + 1 = 2 2 n = 4 n
Let f ( a , b ) = ( a n ) ( b n ) . Note that f ( n + 1 , b ) = 0 because ( n + 1 n ) = 0 .
Observe that ( k n ) ( r n + 1 ) = ( k n ) ( r − 1 n ) + ( k n ) ( r n ) = f ( k , r − 1 ) + f ( r , k ) . Given any a , b satisfying 0 ≤ a ≤ n − 1 , 0 ≤ b ≤ n , we can find exactly one k , r where k < r such that ( k n ) ( r n + 1 ) involves summing f ( a , b ) : indeed, if a ≤ b , then we pick k = a , r = b + 1 , and if a > b , then we pick r = a , k = b .
In other words, we can represent the sum as ∑ a = 0 n + 1 ∑ b = 0 n f ( a , b ) , since we showed each f ( a , b ) appears exactly once somewhere in ( k n ) ( r n + 1 ) .
Since f ( n + 1 , b ) = 0 , we can restrict the sum to ∑ a = 0 n ∑ b = 0 n f ( a , b ) . Now we expand f ( a , b ) and notice that we can factor out ( a n ) , getting ∑ a = 0 n ( ( a n ) ⋅ ∑ b = 0 n ( b n ) ) . But ∑ b = 0 n ( b n ) = 2 n , and we can factor this out of the summation, to get 2 n ⋅ ∑ a = 0 n ( a n ) = 2 n ⋅ 2 n = 4 n .
Problem Loading...
Note Loading...
Set Loading...
Suppose that A tosses n fair coins, and that B tosses n + 1 . Then the probability that A tosses k Heads is 2 − n ( k n ) 0 ≤ k ≤ n while the probability that B tosses r Heads is 2 − n − 1 ( r n + 1 ) 0 ≤ r ≤ n + 1 Thus, if p is the probability that B tosses more Heads than does A , then p = k < r ∑ 2 − n ( k n ) × 2 − n − 1 ( r n + 1 ) and so the sum we are interested in is 2 2 n + 1 p .
The fact that p = 2 1 is a classic problem. Here is a proof.
Let a be the number of Heads that A tosses, and let b be the number of Heads that B tosses. Then a < b ⇔ a + 1 ≤ b ⇔ n − a ≥ n + 1 − b (since a , b are integers) and so P [ a < b ] = P [ n − a ≥ n + 1 − b ] = 1 − P [ n − a < n + 1 − b ] But n − a is the number of Tails that A tosses, while n + 1 − b is the number of Tails that B tosses. In other words, the probability that B tosses more Heads than A is 1 minus the probability that B tosses more Tails than A . By symmetry, the probabilities that B tosses more Heads than A , and that B tosses more Tails than A , must be the same. Hence they are both equal to 2 1 . Thus p = 2 1 , and so the desired sum is 2 2 n = 4 n .